Design and Development of a Pneumatic Bush Installation Tool for Motorcycle Engine Mounting Production Efficiency - Azzahra Nazwa Asyifa; Yuliarto Joko Sumbogo; Dimas Ardiansyah Halim; Joko Suparno (Akademi Inovasi Indonesia, 2024)
The increasing demand for efficient and precise manufacturing processes in the automotive industry has led to the development of automated assembly systems, including pneumatic-based tools. This study focuses on the design, development, and evaluation of a pneumatic Bush installation tool for motorcycle engine mounting production efficiency. The tool was tested against manual methods (hammer and jack) to compare installation time, accuracy, and defect rates (NG). A quasi-experimental approach was used, involving trial and error testing, prototype validation, and comparative analysis. The results showed that the pneumatic system significantly outperformed the manual method, with an 80% improvement in efficiency—reducing installation time from 120 seconds (manual) to 45 seconds (pneumatic). Additionally, Bush misalignment was reduced from 40% (manual) to 10% (pneumatic), while installation-induced defects dropped from 35% to only 5%. The findings demonstrate that the pneumatic-assisted tool provides more consistent pressure control, improved accuracy, and reduced error rates, making it a superior alternative to manual methods. This study contributes to the advancement of automated assembly technologies in the motorcycle manufacturing industry.